A new species of Paramaka Savage & Domínguez, 1992 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) from Brazil - Mariano, Rodolfo (Zootaxa, 2011)
A new species of Paramaka is described based on nymphs and male imagos from State of Mato Grosso, Brazil. The imago of Paramaka pearljam sp. n. can be easily separated from the other species of the genus by the presence of a conspicuous and large median projection with apex curved ventrally on styliger plate; and in nymph by the gills not ended in a thin apical process and tarsal claw without accessory denticles. A new key is proposed and new geographic records for the genus are reported.